Clients’ Perspectives of Risk Management Practice in Malaysian Construction Industry - Mohd Yusuwan, Norazian; Adnan, Hamimah; Omar, Ahmad Faris (2008)
This research is focuses on the practice of risk management (RM) in Client’s organization and aims to identify the level of awareness among construction professionals towards risk management and to examine the policy undertaken when dealing with risks in a construction project. Apart from that, it also aims to identify the problems and challenges for the implementation of risk management in Klang Valley, Malaysia. Questionnaire survey and interviews were carried out in order to obtain a better view on the implementation of risk management in the Malaysian construction industry. It was found that construction professional especially those who are working in client’s organisation are slowly accepting risk management as a management tool that will help in managing a construction project effectively and successfully. Based on the findings of the questionnaires and interviews there are a number of construction professionals who know about risk management and who have attended training and some of them have even practice risk management in their organizations. At least, it has been proven that there are organizations that have implemented risk management in their operations although this is only on a small scale. It can be concluded that risk management still has a long way to go in order to be accepted and recognized in the Malaysian construction industry.